8x-5=7-4x

Simple and best practice solution for 8x-5=7-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-5=7-4x equation:


Simplifying
8x + -5 = 7 + -4x

Reorder the terms:
-5 + 8x = 7 + -4x

Solving
-5 + 8x = 7 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-5 + 8x + 4x = 7 + -4x + 4x

Combine like terms: 8x + 4x = 12x
-5 + 12x = 7 + -4x + 4x

Combine like terms: -4x + 4x = 0
-5 + 12x = 7 + 0
-5 + 12x = 7

Add '5' to each side of the equation.
-5 + 5 + 12x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 12x = 7 + 5
12x = 7 + 5

Combine like terms: 7 + 5 = 12
12x = 12

Divide each side by '12'.
x = 1

Simplifying
x = 1

See similar equations:

| x/3-4=7 | | x(3x-y)(4x+5y)= | | -17+11+6=7t | | 2x+8=-48 | | 7xy^4-7xy^2=0 | | 3n^2-3n-36=0 | | 5(5x+3)=3(8x-2+4) | | x(3x-y)(4x+5x)= | | -7+11+6=7t | | 2x+25=-2x-7 | | 6(x-2)=14 | | 3x-39=75 | | 5=7t | | -4x+(-2x+6)=9 | | 13x+23=2x-13 | | -3x-8=x+16 | | -6x+2(x+6)=42 | | k-5k=-40 | | -3x-19=5+x | | -3x-19=5+5 | | 2x-1/4=5 | | x-1+7x+55=2x-1 | | (2x+y)(x^2+3xy-2y^2)= | | -4x+4(-4x-11)=46 | | 0.2x+2.4=1.5+1.2x | | (5x^2+8x)(15x^2-7x-4)=0 | | 2-6(a-7)=-(1+a) | | 3x+10=-5-2x | | x^2+4x-36=0 | | 6n=4(n+5)+2n | | 10[z-(9z+42)+2]=5z+25 | | 3x-11=-4x+10 |

Equations solver categories